Dissipation of electron-beam-driven plasma wakes - Rafal Zgadzaj (Nature Portfolio, 2020)
Plasma wakefield accelerators promise compact, affordable future particle accelerators, but require deposition of enormous energy into a small volume. Here, the authors measure and simulate how this energy transfers from the wake into surrounding plasma, a process that ultimately governs the accelerator’s repetition rate.